Iterative Volumetric Reduction (IVR) Steered Response Power Method for Acoustic Source Localization - Boora, Ritu; Dhull, Sanjeev K. (International Journal of Sensors Wireless Communications and Control, 2021)
Background: The Steered Response Power–Phase Transform (SRP-PHAT) approach is a breakthrough in the field of source localization in a high reverberant environment, but the substantial computational cost limits its usage in the practical implementation. Objective: This paper presents an efficient SRP-PHAT based, Iterative Volumetric Reduction (IVR) Steered Response Power method for acoustic source localization in non-ideal surroundings. Methods: Developing the coarse acoustic maps in the preliminary iterations provides a measure of the approximate likelihood of a source lying in the corresponding regions. Subsequently, the search space volume is reduced to the region containing points with significant likelihood. Furthermore, these two steps are iterated to achieve the desired resolution. Results and Conclusion: Conclusively, the computational load reduces by 60-80% with considerable upgrading in accuracy as compared to Modified SRP PHAT. The required functional evaluation is adaptable to the environment, which makes it an excellent approach over Iterative modified SRP-PHAT in unfavourable circumstances. Experiments conducted in various scenarios demonstrate the method's significance over the other state–of-the-art methods.
Keywords: Modified SRP-PHAT